KALENDER UMM AL-QURA (Studi Pergeseran Paradigma Sistem Kalender di Kerajaan Arab Saudi) - Musonnif, Ahmad (Ahkam: Jurnal Hukum Islam, 2015)
Umm Al Qura calendar is a new calendar issued by the Saudian Kingdom for civil purpose which is based on hisab (based on computation) system. The reason for issuing such kind of calendar is to unite Moslems all over the world especially in deciding the first day of Ramadhan, Idul Fitri, and Idul Adha. The hisab system of Umm al Qura calendar often leads to a controversy because it comes up with different result in determining the first day of a month compared to the other calendars which use rukyat (based on observation) system. However, this kind of calendar is widely adopted in the areas where Moslems are minority. Kata kunci: Kalender Umm al-Qura, Pergeseran Paradigma, Sistem Kalender Kerajaan Arab Saudi